Chrysen-2-ol derivative from West Indian wood nettle Laportea aestuans (L.) Chew inhibits oxidation and microbial growth in vitro - Oloyede, Ganiyat K.; Oyelola, Martha S. (Technische Universität Dortmund, 2013)
Bio-active compounds present in West Indian Wood Nettle Laportea aestuans (L.) Chew (Urticaceae), used in ethno medicine as antioxidant and antimicrobial were studied. The aim of this research work was to isolate and characterize the bio-active compounds in the n-hexane fraction of L. aestuans, determine the toxicity and subject it to in-vitro antimicrobial and free radical scavenging activities. The chemical constituents were isolated by gradient elution column chromatographic technique and Ultra Violet/visible (UV), Infrared (IR) and Nuclear Magnetic Resonance (NMR) spectroscopies were used for structural elucidation. The free radical scavenging activity of the isolate was assessed using three methods; scavenging effect on 2,2-diphenyl-1-picrylhydrazyl radical (DPPH), hydroxyl radical generated from hydrogen peroxide and ferric thiocynate method. Antimicrobial screening was done by agar well diffusion method while toxicity was determined by Brine shrimp lethality test. Structures were proposed for the white crystalline solids isolated; (4E)-3,6-dimethylhep-4-en-3-ol (AB) and 1,2,3,4,4a,4b,5,6,6a,7,8,9,10,10a,10b,11-hexadecahydro-1,1,6a,10b-tetramethyl-7-((E)-4,7-dimethyloct-5-enyl) chrysen-2-ol (AC). Percentage yield of AC was 91.2 and was non-toxic with LC50 (μg/ml) value of 1581233000.0. AC significantly scavenged free radical at 0.0625 mg/ml in the DPPH (64.73 %) and hydrogen peroxide (99.22 %) tests. It also showed 65.23 % inhibition at 1.0 mg/ml in the ferric thiocyanate test. AC also inhibited microbial growth significantly when compared with gentamicin and tioconazole which are antibacterial and antifungal standards respectively. The presence of Chrysen-2-ol derivative in L. aestuans which was non-toxic and possessed significant antimicrobial and antioxidant activities supports its ethno medicinal application.
EXCLI Journal ; Vol. 12, 2013
Keywords: Laportea aestuans; (4 E )-3,6-dimethylhep-4-en-3-ol; chrysen-2-ol; toxicity; antimicrobial; antioxidant; 610